A Kut Prisoner - Bishop, Harry Coghill Watson (Salt Lake City, UT : Project Gutenberg, 2010)
"A Kut Prisoner" by Harry Coghill Watson Bishop is a historical account written in the early 20th century. The narrative recounts the personal experiences of a subaltern in the Indian Army Reserve during the First World War, specifically detailing the battles faced and the subsequent captivity at Kut followed by an arduous escape from Turkey. Readers can expect a detailed depiction of military life, the challenges of war, and the resilience of soldiers, framed through the author's firsthand observations. The opening of the narrative introduces the protagonist's initial journey from India to Basra, where he joins a regiment and anticipates joining the front lines amidst the Turko-British conflict in Mesopotamia. Bishop conveys a palpable sense of military camaraderie as he describes the experiences leading up to the battle of Ctesiphon, emphasizing the excitement, uncertainty, and the grim realities of war as the British forces encounter the well-prepared Turkish troops. The text captures the disorienting nature of warfare and sets the tone for the trials and tribulations that will unfold as the soldiers face both enemy fire and the challenges of survival in captivity. (This is an automatically generated summary.)
Release date is 2010-10-14
E-text prepared by David Clarke, Linda Hamilton, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/Canadian Libraries (http://www.archive.org/details/toronto)
Keywords: World War, 1914-1918 -- Personal narratives, English; World War, 1914-1918 -- Prisoners and prisons, Turkish